Utilization of Egg-shell, a Locally Available Biowaste Material, for Adsorptive Removal of Congo Red from Aqueous Solution - Shahanaz Parvin; Al- Mamun; Md. Fazle Rubbi; Md. Abdur Ruman; Md. Moshiur Rahman; Biplob Kumar Biswas (Aceh International Journal of Science and Technology, 2020)
Egg-shell, a locally obtainable biowaste material, was successfully used for common textile dye (congo red) removal from synthetic wastewater solution. All adsorptive experiments were carried out in a batch method. Experiments were conducted to understand the consequence of different functioning parameters, for example, the pH of the solution, adsorbent dosage, reaction time, and initial adsorbate concentration. The surface morphology of the egg-shell was analyzed by scanning electron microscopy (SEM) images of the adsorbent (before as well as after adsorption) showed that there was a change in surface morphology, which ensured the congo red adsorption on the adsorbent surface. The adsorbent dose was determined to be 1g as optimum value, while the solution pH 5 was seemingly the best operating pH at the tested conditions. Complete adsorption was achieved in 120 min while the pseudo-second-order kinetic model portrayed the sorption kinetics quite nicely. Langmuir adsorption model (monolayer adsorption) was the best-suited model for describing the sorption process in the concern of the correlation coefficient. The values of dimensionless separation parameters (RL) signified that the adsorption process was promising for all studied concentrations. A considerably great extent of sorption capacity (153.85 mg/g) of egg-shell adsorbent indicated that it could be employed for wastewater treatment in textile and related industries